Talent marketplaces: job architecture, productivity, and employee engagement - Jesuthasan, Ravin (Henry Stewart Talks, 2026)
Talent marketplaces, Corporate structure, Democratization of work, Skill supply and demand, Unilever, Job architecture, HR, AI, Bias, Privacy